Pengaruh Persepsi Manfaat, Kepercayaan, dan Kemudahan Penggunaan terhadap Minat Menggunakan QRIS.docx - Farhan Saifudin; Bima Satriawan; Irfan Amali; Mario Eko; Zyan Kalla (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of perceived benefits, trust perception, and perceived ease of use on the interest of MSME actors in using the QRIS payment system in Surakarta. The research method used is a survey with a quantitative approach, where data is collected through questionnaires distributed to MSME actors in Surakarta. Data analysis is conducted using multiple linear regression tests with the help of EViews software. The results of the study indicate that perceived benefits, trust perception, and perceived ease of use significantly influence the interest of MSME actors in using QRIS. Perceived benefits and trust perception have the greatest influence, followed by perceived ease of use. Based on these findings, it is recommended that relevant parties enhance socialization and education regarding the benefits, security, and ease of use of QRIS to encourage broader adoption among MSME actors